2005
DOI: 10.1080/16506070510043750
|View full text |Cite
|
Sign up to set email alerts
|

Combining Pharmacotherapy with Cognitive‐Behavioral Interventions for Obsessive‐Compulsive Disorder

Abstract: This paper reviews the evidence-based literature concerning the efficacy and effectiveness of cognitive behavior therapy (CBT), drug treatment and their combination for obsessive compulsive disorder (OCD). After a brief outline of the seminal studies, the state of the art is presented with reference to the consensual recommendations proposed in the last 10 years. Management of OCD rests on potent selective serotonin reuptake inhibitors and CBT, used separately, sequentially, or concurrently. A hierarchical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 36 publications
(32 reference statements)
1
19
0
2
Order By: Relevance
“…In the case of insufficient response to this intervention and/or severe OCD symptomatology a combination with psychopharmacotherapy is recommended (Cottraux et al 2005 ;Eddy et al 2004), preferably with selective serotonin reuptake inhibitors (SSRIs), which are currently considered as drugs of first choice in OCD (APA, 2007 ;Bandelow et al 2008 ;Fineberg et al 2012 ;National Institute for Clinical Excellence, 2006). A Cochrane review comprising 17 randomized controlled trials (RCTs) could not identify any significant differences in the efficacy of citalopram, fluoxetine, fluvoxamine, paroxetine and sertraline (Soomro et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of insufficient response to this intervention and/or severe OCD symptomatology a combination with psychopharmacotherapy is recommended (Cottraux et al 2005 ;Eddy et al 2004), preferably with selective serotonin reuptake inhibitors (SSRIs), which are currently considered as drugs of first choice in OCD (APA, 2007 ;Bandelow et al 2008 ;Fineberg et al 2012 ;National Institute for Clinical Excellence, 2006). A Cochrane review comprising 17 randomized controlled trials (RCTs) could not identify any significant differences in the efficacy of citalopram, fluoxetine, fluvoxamine, paroxetine and sertraline (Soomro et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…An individual patient with poor response should receive a trial with both modalities. With greater severity of OCD, it may be advisable to add medications (Cottraux et al 2005).…”
Section: )(E)mentioning
confidence: 99%
“…Our own study found people who received CBT with or without medication were less likely to relapse. 2 In this context, the paper by Tenneij et al brings new interesting conclusions on the combined approach. The novel approach used in this RCT was to initiate CBT in people who were responders to an adequate trial of venlafaxine or paroxetine.…”
Section: Commentarymentioning
confidence: 98%